Trauma by the Numbers: A Cross-Sectional Analysis and Categorization of Trauma Cases in the Gaza War - Muaaz Wajahath; Muaaz Wajahath; Elias Nasser; Elias Nasser; Tariq Nayfeh; Bilal Irfan; Bilal Irfan; Bilal Irfan; Bilal Irfan; Rohit Balasundaram; Mosab Nasser; Khaled J. Saleh; et al. (International Journal of Public Health)
ObjectivesTo categorize and analyze trauma cases from the Gaza war, identifying injury patterns and informing future humanitarian efforts in conflict zones.MethodsA cross-sectional study was conducted in April 2024 at European Gaza Hospital. Data on demographics and injury types were collected from patients treated by FAJR Scientific’s surgical team. Injuries were classified into primary (directly conflict-related), secondary (indirectly conflict-related), and tertiary (unrelated to the conflict). Statistical analyses included Kruskal-Wallis H test, logistic regression, and Fisher’s Exact Test.ResultsAmong the 80 surgical cases analyzed, primary injuries were the most common (53%), predominantly affecting males aged 30–39. Secondary injuries accounted for 14% of cases, while tertiary injuries represented 33%. Significant associations were found between age categories and injury classifications (p < 0.05).ConclusionThe prevalence of primary injuries highlights the severe impact of conflict on civilians, particularly middle-aged males. The findings suggest the need for enhanced orthopedic surgical capacity, integrated chronic disease management, and specialized pediatric care in conflict zones. Improved data collection and analysis are essential for optimizing medical interventions and resource allocation.